Автоматизация проектирования печатных блоков с модулями произвольной формы - Герасименко Е. П. Евгений Петрович; Кот В. И. Владимир Иосифович; Ландау И. Я. Игорь Яковлевич; Сомкин В. М. Василий Михайлович (Москва, Машиностроение, 1979)
Исключено из фонда НТБ ТПУ